Application Of Hypertension Gymnastics Against High Blood Pressure For The Elderly In Bendungan Village, Sragen - Ardyantilova, Kharismaputri; Lidiana, Exda Hanung (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Background: Hypertension is the most common vascular disease in society. According to data from the World Health Organization (WHO) in 2021, the prevalence is 1.28 billion people with hypertension aged 30-79 years. The elderly is the age limit that is most vulnerable to suffering from hypertension. Hypertension Gymnastics is an appropriate non-pharmacological treatment for the elderly because the movements tend to be slow but show significant results. Objective: To know the results of the implementation of Hypertension Gymnastics on changes in blood pressure in elderly people with hypertension. Method: This application uses a method in the form of a case study with a sample of two respondents in Dukuh Tegalsari, rt.002/000, Bendungan, Kedawung, Sragen, each of whom suffers from mild hypertension. Results: The management of hypertension in the elderly with Hypertension Gymnastics, which was given twice a week for 30 minutes and carried out for a total of four weeks, decreased in the first respondent by a decrease in systolic by 22 and a decrease in diastolic by 14, while in the second respondent, there was a decrease in systolic by 23 and a diastolic decrease of 13 in the normotensive category. Conclusion: Hypertension Gymnastics in the elderly can reduce blood pressure in elderly with hypertension.